Holistic investigation of macroalgal species richness along the Southern Atlantic Coast of Morocco - Boutafda, Aziz; Akkari, Majdouline; Ben Bakrim, Widad; Mazar, Adil; El Kharrassi, Youssef; Elarroussi, Hicham; Ouhdouch, Yedir; Hafidi, Mohamed; Kouisni, Lamfeddal; Ezzariai, Amine (Frontiers in Marine Science, 2025)
This study investigated the biodiversity of macroalgae along the southern Atlantic coast of Morocco and explored the relationship between their distribution and the physicochemical properties of seawater. The study identified a total of 21 macroalgal species, classified into 19 genera, 14 families, and 9 orders. The distribution of these species along the coast was analyzed, revealing 8 dominant species that collectively made up approximately 64.7% of the macroalgal flora. These dominant species belonged predominantly to the Florideophyceae (75%) and Phaeophyceae (25%) families. Gracilariaceae and Rhodomelaceae families exhibited high species diversity, accounting for 28.57% of all observed species. The equitability index indicated variations in species distribution and dominance among different sites. Chemical characterization indicated that the concentrations of available phosphorus in the seawater ranged from 0.2 to 0.6 mg/L, while the chlorophyll-a content in the macroalgae varied between 1.2 and 2.8 mg/g. Additionally, the total phenol content in the algae ranged from 2 to 5 mg/g. Gas chromatography-mass spectrometry (GC-MS) analysis of macroalgae revealed the presence of diverse compounds such as fatty acid, phytyl-eicosanoate, and sterols. These findings highlighted the interactions between the marine environment’s characteristics and algal diversity, while exploring some key parameters of algal growth and composition. The obtained results could help the scientific community to identify several strategies for both algal biodiversity and biorefinery.